ANALYSIS OF THE MAIN FACTORS FOR THE DIGITALIZATION OF HIGHER EDUCATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The implementation of digital technologies and the global network impacts virtually all areas of life in the modern world. Higher education is no exception, and this requires an analysis of the entry of new technologies into education, as well as a review of existing strategic documents at the national and European level.  The digital transformation is becoming a critical organizational strategy for survival and achieving competitiveness in higher education. The aim of the scientific paper is to identify the main factors influencing the process of digitalization and to mark the progress of the EU member states in this field. Descriptive and comparative analysis have been used in the study, applying quantitative data review. The analysis includes the political, socio-economic, organizational, educational and technological factors that influence the process of digitalization of higher education.